2019
DOI: 10.7717/peerj.6769
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the NaCl-dependent behavior of hydrogen production of a marine bacterium,Vibrio tritonius

Abstract: Biohydrogen is one of the most suitable clean energy sources for sustaining a fossil fuel independent society. The use of both land and ocean bioresources as feedstocks show great potential in maximizing biohydrogen production, but sodium ion is one of the main obstacles in efficient bacterial biohydrogen production. Vibrio tritonius strain AM2 can perform efficient hydrogen production with a molar yield of 1.7 mol H2/mol mannitol, which corresponds to 85% theoretical molar yield of H2 production, under saline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 65 publications
(91 reference statements)
0
1
0
Order By: Relevance
“…Previous studies have indicated that NaCl acts as an inhibitory factor in biotechnological processes, such as anaerobic digestion [26], or hydrogen production [41] that are reliant on the performance of robust mixed cultures. However, increased salinity was also associated with J o u r n a l P r e -p r o o f increased solubilization of carbohydrates and subsequently enhanced production of L-versus Dlactic acid in a heterofermentative process using food waste [5].…”
Section: Salinity Evolved Bacterial Strains Maintain Initial Lactic A...mentioning
confidence: 99%
“…Previous studies have indicated that NaCl acts as an inhibitory factor in biotechnological processes, such as anaerobic digestion [26], or hydrogen production [41] that are reliant on the performance of robust mixed cultures. However, increased salinity was also associated with J o u r n a l P r e -p r o o f increased solubilization of carbohydrates and subsequently enhanced production of L-versus Dlactic acid in a heterofermentative process using food waste [5].…”
Section: Salinity Evolved Bacterial Strains Maintain Initial Lactic A...mentioning
confidence: 99%